B cell–intrinsic CXCR3 drives efficient generation of ectopic pulmonary germinal center responses to influenza A virus infection - Timona S. Tyllis; Todd S. Norton; Caitlin Abbott; Dylan J. McPeake; Kevin A. Fenix; Jasmine J. Wilson; Ervin E. Kara; Kim L. Good-Jacobson; Mohammed Alsharifi; Shaun R. McColl; Iain Comerford (Proceedings of the National Academy of Sciences, 2026)
Chemotactic receptors involved in generation of ectopic pulmonary germinal centers (GCs) within inducible bronchus-associated lymphoid tissue (iBALT) are poorly defined. Here, using CIBER Cxcr3 -reporter mice, we demonstrate that the prototypical type 1 inflammatory chemokine receptor CXCR3 is highly induced in influenza A virus (IAV)-reactive B cells in the mediastinal lymph node, spleen, lung, peripheral blood, and airways following intranasal infection. Notably, elevated Cxcr3 was observed in ectopic pulmonary germinal center B (GCB) cells in iBALT relative to their contemporaneous counterparts in secondary lymphoid organs across the timecourse of the response to IAV infection. Mice with a B cell–specific deletion of Cxcr3 displayed a 50 to 60% reduction in the frequency and number of ectopic GCB cells in the lungs at the peak of the response following IAV infection, relative to controls. Furthermore, in cotransfers, Cxcr3 -deficient B cells were substantially outcompeted by their Cxcr3 -sufficient counterparts for ectopic pulmonary GC participation, but were not impacted with respect to GCB cell frequencies in other compartments. Thus, the data elucidate the requirement of B cell–intrinsic CXCR3 expression for efficient generation of ectopic pulmonary GCB cell responses in iBALT following respiratory viral infection with IAV, a finding that broadens understanding of the molecular cues underpinning this key component of local protective humoral immunity to IAV.